Preferensi Diaphorina citri Kuwayama (Homoptera: Psyllidae) pada Beberapa Jenis Tanaman Jeruk - WIJAYA, I NYOMAN (AGRITROP; Vol. 26, No. 3 September 2007)
The research was conducted at Laboratory Pest and Disease, Faculty of Agriculture Udayana University. The purpose of the research were to investigate preference of Diaphorina citri on the diference kind of host plant. The result of of this study showed that D. citri highly prefers CVPD infected citrus cv. siam, but the highest fecundaty of D. citri was on kemuning plant. Population growth of D. citri performed highly at CVPD infected citrus cv. siam and kemuning.
Keywords: Preference, fecundaty, population growth, diference kind of host plant, D. citri